Guidelines for Proactive Home Elderly Health Care by Nurses at Tambon Health Promoting Hospitals in Thailand - Wongprasit, Nawasanan; Thummikkaphong, Sureeporn; Tantinantrakun, Supaporn (Journal of Preventive Medicine Association of Thailand, 2023)
Thailand has become an aging society more than 10 years. As advanced medical science extends people’s lives and infant births also reduce, the proportion of the aging population grows. When people get older, their organs are more active and tend to deteriorate more easily and faster. Therefore, it is a factor that the elderly must receive more health care according to their age as well. In addition, the nature of the elderly in Thai society prefers to live at home from birth to old age and would rather die among relatives and friends in the village than die in the hospital. As a result, there is an increasing demand for home care for the elderly who have health issues and/or need to be visited more frequently in order to provide continuous care at home, as well as technological changes. Home care guidelines must be adjusted to accommodate advances in science, society, economy, environment, health beliefs, incidence, epidemics, and emerging diseases. Therefore, proactive home elderly health care has emerged as an important strategy for promoting elderly health care. In addition, nurses who take care of the elderly at home have an opportunity to be close and informed of all problems affecting the quality of life of the elderly. It makes mutually finding causes of illness together and solving problems more relevant to the needs of the elderly. The purpose of this article was to present guidelines for proactive home elderly health care from nurses who worked at Thailand’s Tambon Health Promoting Hospital. As a result, the elderly will have a higher quality of life and families will be more satisfied.